Multifocal retiform hemangioendothelioma of bone masquerading as skeletal metastasis - Narang, Neha Chopra; Narang, Salil; Venugopal, Vasantha Kumar (Indian Journal of Case Reports, 2018)
Hemangioendothelioma (HE) is a rare primary bone tumor of vascular origin constituting 0.5–1% of primary malignant bone tumors. Here, we report the clinical and histopathological features of a 38-year-old male who presented with multifocal lesions involving the left scapula, left proximal humerus, and the left ulnar olecranon process which was diagnosed as metastatic lesion radiologically and clinically. The final diagnosis of retiform HE was made on the basis of histopathology.